Clinical frailty and performance scale translation in palliative care: scoping review. Issue 3 (1st June 2022) - Dewhurst, Felicity; Stow, Daniel; Paes, Paul; Frew, Katherine; Hanratty, Barbara
Abstract : Background: Frailty is associated with advancing age and increases the risk of adverse outcomes and death. Routine assessment of frailty is becoming more common in a number of healthcare settings, but not in palliative care, where performance scales (eg, the Australia-modified Karnofsky Performance Status Scale (AKPS)) are more commonly employed. A shared understanding of performance and frailty measures could aid interspecialty collaboration in both end-of-life care research and clinical practice. Aims: To identify and synthesise evidence comparing measures of performance routinely collected in palliative care with the Clinical Frailty Scale (CFS), and create a conversion chart to support interspecialty communication. Methods: A scoping literature review with comprehensive searches of PubMed, Web of Science, Ovid SP, the Cochrane Library and reference lists. Eligible articles compared the CFS with the AKPS, Palliative Performance Scale (PPS), Karnofsky Performance Scale or Eastern Cooperative Oncology Group Performance Status or compared these performance scales, in patients aged > 18 in any setting. Results: Searches retrieved 3124 articles. Two articles directly compared CFS to the PPS. Thirteen studies translated between different performance scores, facilitating subsequent conversion to CFS, specifically: AKPS/PPS 10/20=very severe frailty, AKPS/PPS 30=severe frailty, AKPS/PPS 40/50=moderate frailty, AKPS/PPS60=mild frailty. Conclusion: We present a tool for converting between the CFS and performance measures commonly used in palliative care. A small number of studies provided evidence for the direct translation between CFS and the PPS. Therefore, more primary evidence is needed from a wider range of population settings, and performance measures to support this conversion.